Corrigendum to “Effects of handwriting exercise on functional outcome in Parkinson disease: A randomized controlled trial” [J Clin Neurosci 72C (2020) 298–303] (Journal of Clinical Neuroscience (2020) 72 (298–303), (S096758681931433X), (10.1016/j.jocn.2019.08.119)) - Nisa Vorasoot (2020)
© 2020 Elsevier Ltd The authors regret that there was a typographical error in the time used to complete the 1st handwriting test (T1) (seconds), mean (SD) in the control group (in the first row of the data in Table 2) that was originally published. The correct value is 169.83 (50.97). The authors would like to apologise for the error.